2020
DOI: 10.1155/2020/8855335
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Instability Characteristics and Bolt Support in Deep Mining Roadways Based on the Surrounding Rock Stability Index: Example of Pansan Coal Mine

Abstract: In view of the influence of mining stress on the stability of the surrounding rock of inclined roof mining roadways in deep mines, the surrounding rock stability index is defined and solved based on the rock strength criterion and the stress distribution. The mining roadway of the 17102(3) working face of the Pansan Coal Mine is used as the engineering background and example. The surrounding rock’ stabilities under the conditions of no support and bolt support are analyzed according to the surrounding rock’s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Wang et al (2018) found that when the anchorage length of the bolt is fixed, the effective compressive stress area in the surrounding rock of the non-anchored portion increases with the increase of the pretension. Chang et al (2020) defined the surrounding rock stability index and then studied the stability of the surrounding rock with different anchorage lengths. They found that the full-length anchoring bolt support reduces the area of instability to a greater extent, compared to the end-anchoring bolt support.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2018) found that when the anchorage length of the bolt is fixed, the effective compressive stress area in the surrounding rock of the non-anchored portion increases with the increase of the pretension. Chang et al (2020) defined the surrounding rock stability index and then studied the stability of the surrounding rock with different anchorage lengths. They found that the full-length anchoring bolt support reduces the area of instability to a greater extent, compared to the end-anchoring bolt support.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, the proportion of bolt support is low (less than 30%), and for complex and difficult roadways, such as in Guizhou mining area, for a large number of complex roof conditions, shed support was used in the roadway only basically. Practice has proved that as passive support, shed support cannot effectively restrain the large deformation of composite roof, the support and maintenance costs are high, and roof fall accidents occur frequently, which seriously threaten the safety production of the mine [12][13][14][15][16]. Therefore, to carry out research on the stability mechanism of roadway surrounding rock under the condition of composite roof, a scientific and reasonable mechanical structure model was established, and the adaptability of bolt support technology was theoretically explored under this condition, which is a useful attempt to promote the development of roadway excavation technology, with important theoretical value and practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Chang and others defined the surrounding rock stability index and then studied the stability of the surrounding rock with different anchorage lengths. They found that the full-length anchoring bolt support reduces the area of instability to a greater extent, compared to the end-anchoring bolt support [10]. Zou and Zhang studied the dynamic evolution characteristics of bond strength between bolt and rock mass under axial tensile load, and the mechanical behavior of fully grouted bolt considering the uneven surrounding rock stress around the bolt [11].…”
Section: Introductionmentioning
confidence: 99%